A new species of the genus Barsura Volynkin, Dubatolov & Kishida from China (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V. (Zootaxa, 2018)
The genus Barsura Volynkin, Dubatolov & Kishida, 2017 belongs to the tribe Lithosiini, subfamily Arctiinae, family Erebidae, and was recently erected for Barsine nubifascia Walker, [1865] and its allies (Volynkin et al. 2017). At present the genus includes ten valid species distributed in Himalaya (Pakistan, Nepal, northern and northeastern India, Bhutan), China and North Vietnam (Volynkin et al. 2017; Volynkin 2017). During studies of extensive Lithosiini materials deposited in Museum Witt / Zoologische Staatssammlung, München (Munich, Germany), I found a short series of one more, yet undescribed species from the Chinese province Sichuan. The description of the new species is presented below.